“P’rá ver a banda passar”: uma etnografia musical da Banda Marcial Castro Alves - Souza, Erihuus de Luna (2010)
This work can be divided into four parts. The first part consists in references of theoretical and methodological and contains two chapters. The first chapter contextualizes the marching bands, presenting and describing the methodological procedures used to perform this work, as well as the rationale and literature review. This is the theoretical framework that supports the analysis and subsequent discussion. The second chapter presents the bands in a broad sense and diachronic, since his arrival in Brazil and the course of this story, through Paraíba, definitions of musical bands, the fanfare and marching bands to achieve the specificity of BMCA - Banda Marcial Castro Alves - style and drum corp. The second part consists of the presentation, analysis and discussion of the dice, involving the third chapter, which contextualizes the relationship with the band's social environment, interaction with the community and the school. The fourth chapter presents the transformation of the drum corp fanfare, the BMCA. The third part that covers five chapters describing the forms of admission, teaching and learning music in BMCA, in the form of a daily test.The sixth chapter reports the daily presentations that followed and analyzed during the research, from presentations in theaters, parades and competitions to my participation as a musician in the band. Part Four, chapter seven analyzes of works in styles representative, composed or arranged for bands to BMCA. The final consideration presents some conclusions and possible research contributions.